PERSECUTION TOWARDS HAZARA PEOPLE IN AFGHANISTAN ACCORDING TO INTERNATIONAL HUMAN RIGHTS LAW - , ANASTASIA VICENT WIDYA PANGESTIKA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Hazara is an ethnic minority in Afghanistan with Mongol tribes and live in the central highland region of Afghanistan known as Hazarajat. Unlike the majority of the region that is considered Sunni Islam, Hazara is overwhelmingly Shia. These differences became the main reason of Taliban to prosecute them. Persecution of Hazara people refers to systematic discrimination, ethnic cleansing and murder. The violations toward Hazara breach the principles that laid down in Universal Declaration of Human Rights 1948 and International Covenant on Civil and Political Rights. This research is using normative legal research as the method, which means that the writer collects the data altogether through literary studies such as laws and regulations, books, journal, and other valid information that are related to the research. The writer applies a normative approach to discover the general principles of law and examines how International Human Rights law can be applied in the case study of persecution of Hazara. Regarding to the result of this research, the writer can conclude that Afghanistan is fully responsible towards Hazara as a victim of persecution. In this regard, the Taliban who replace government of Afghanistan worsen the persecution towards Hazara. The presence of new Afghanistan Constitution of 2002 should be an opportunity of Afghanistan government in order to reaffirm faith in fundamental human rights, in the dignity and worth of the human person and in the equal rights of citizens and to promote the protection of human rights in Afghanistan. The establishment of Afghanistan Independent Human Rights Commisions (AIHRC) based on Afghanistan Constitution of 2002 should be one of the ways to help Hazara in guaranteeing their rights.